Systems biology in the central nervous system: A brief perspective on essential recent advancements. Issue 3 (June 2017) - Dougherty, Joseph D.; Yang, Chengran; Lake, Allison M.
Abstract: As recent advances in human genetics have begun to more rapidly identify the individual genes contributing to risk of psychiatric disease, the spotlight now turns to understanding how disruption of these genes alters the brain, and thus behavior. Compared to other tissues, cellular complexity in the brain provides both a substantial challenge and a significant opportunity for systems biology approaches. Current methods are maturing that will allow for finally defining the 'parts list' for the functioning mouse and human brains, enabling new approaches to defining how the system goes awry in disorders of the CNS. However, the availability of tissue is certainly a challenge for systems biology of neuroscience, compared to systems biology of other tissues, where biopsy is feasible. This challenge is particularly notable for disorders caused by extremely rare genetic variants. Thus computational and systems biology approaches, as well as precise experimental models by way of genome editing, will play key roles in defining mechanisms for disorders, and their individual symptoms, across varied genetic etiologies. Here, we highlight recent progress in neurogenetics, postmortem genomics, cell-type specific profiling, and precision modeling toward defining mechanisms in disease. Graphical abstract: Highlights: Large subject numbers are yielding substantial numbers of new loci and gene associations for CNS disorders. Massively parallel functional assays have potential for defining relevant polymorphisms within disease loci. Systematic approaches are also maturing for using chromatin annotations for defining relevant polymorphisms. Postmortem transcriptomic data is being leveraged to identify corresponding cellular deficits in CNS disorders. Advances in single cell profiling methods are poised to contribute substantially to our understanding of disease.